Exogenous melatonin enhances Lr10-mediated resistance to Puccinia triticina by upregulating TaRAR1 and potentiating salicylic acid pathway and antioxidant defense system - Johannes Mapuranga; Lulu Song; Ruolin Li; Hao Li; Jiaying Chang; Jiaojie Zhao; Yingdan Zhang; Na Zhang; Wenxiang Yang (Plant Stress)
Wheat leaf rust, caused by the biotrophic fungal pathogen Puccinia triticina (Pt), continuously threatens global wheat production, causing considerable yield losses necessitating the implementation of effective management approaches. While conventional breeding and chemical control strategies have been used, priming agents and genetic regulators offer sustainable strategies for wheat leaf rust management. Melatonin (N-acetyl-5-methoxytryptamine), a pleiotropic signaling molecule, induces plant innate immunity against abiotic and biotic stresses. This study demonstrates that exogenous melatonin (100 µM) enhances Lr10-mediated resistance to wheat leaf rust by upregulating TaRAR1, salicylic acid downstream genes, antioxidant enzyme genes, MAPK cascade genes, and WRKY transcription factors during Pt infection. RAR1 serves as an initial convergence point in signaling pathways activated by several R genes. Herein, TaRAR1 was strongly upregulated during early stages of infection in incompatible interactions, and this was associated with increased endogenous SA and melatonin levels, correlating with enhanced defense responses. TaRAR1 silencing compromised TcLr10 resistance, reducing SA and melatonin levels, downregulating defense-related genes, and altering reactive oxygen species dynamics by increasing TaCAT expression and reducing hydrogen peroxide accumulation. TaRAR1 silencing also downregulated TaSGT1, and TaHSP90, suggesting its role in stabilizing NLR proteins. In conclusion, melatonin augments wheat resistance to leaf rust by upregulating TaRAR1, SA signaling, and antioxidant defenses, with MAPK cascades and WRKY transcription factors amplifying downstream responses. This study provides novel insights into the integration of phytohormonal and genetic approaches for enhancing wheat resistance to leaf rust, offering strategies for sustainable disease management.